Fabrication, microstructure, and nonlinear/linear optical parameters of polymeric‐based poly(vinyl alcohol)/poly(vinyl pyrrolidone) nanocomposites films for optical attenuation applications. (8th July 2022) - Nawar, Ahmed Mahmoud; Ali, Haitham Elhosiny; Khairy, Yasmin; Awwad, Nasser Sayed; Algarni, Hamed; Shakir, Mohamed; Sayed, Mahmoud Ahmed; Fawy, Khaled Fahmi; Alderhami, Suliman Ahmed; Abdel‐Aziz, Mohamed
Abstract: Herein, a novel proposed optical attenuator poly(vinyl alcohol)/poly(vinyl pyrrolidone) (PVA/PVP) doped PbS (NPs) nanoparticles nanocomposites films. The samples are fabricated by casting‐method to analyze the linear optical properties and estimate the nonlinear optical parameters. The crystal and molecular structure of the fabricated nanocomposites thick (PVA/PVP) films of different PbS (NPs) doping ratios were analyzed by XRD technique and FT‐IR, respectively. The semi‐crystalline nature of the fabricated PVA/PVP is influenced through all samples and the crystallinity is increased. The particle size of PbS (NPs) is increased in the doped samples and the strain parameter is increased. The measured transmission of the fabricated PVA/PVP doped PbS (NPs) films are decreased as the doping ratio of PbS (NPs) is increased. The absorption coefficient is incremented and shows large absorption values in the UV regions, may be utilized in UV‐blocking for saving the human skin, dramatically, and a noticed red‐shift in the edge of absorption for all samples as the doping ratio is increased. The most probable transition is indirect, and the evolved values of the energy gaps between HOMO and LUMO levels are decrement from 3.97 to 2.65 eV as doping ratio of PbS (NPs) is increased. Different models are utilized to evaluate the average values of the real refractive index (2.175–2.438). The fabricated PVA/PVP doped PbS (NPs) samples are investigated for normal light and laser attenuations. The mass attenuation coefficient increases, gradually, with increment of PbS (NPs), but the half value layer (HVL) parameter decreases with increasing of the doping ratio. These experimental results confirm the applicability of the fabricated samples to attenuate Red‐632 nm and Green‐532 nm laser radiation. It is possible to utilize PVA/PVP doped PbS (NPs) nanocomposites in different, wide‐scale optical filters.